Formulasi Brownies Berbasis Tepung Kacang Hijau dan Puree Kulit Pisang Raja Sebagai Makanan Selingan Tinggi Kalium - Msy . Miranda; Manuntun Rotua; Susyani Susyani (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Brownies is one kind of cake which is popular in public, it has brown color, unexpand with a sweet taste and chocolate flavor. So it can be used as an alternative ways to adding other ingredients on food products to increase nutrient content especially potasium. Hypertension is a condition where the increase in systolic blood is above the normal limit, namely > 140 mmHg and diastolic blood pressure > 90 mmHg. Examples of food sources of potassium are bananas, potato, sweet potato, tomato, red beans, advocado, seafood, and milk. This study was conducted from March-April 2023. This study was conducted using a non-factorial completely randomized design (CRD). The results showed that the selected brownies was the F3 brownie formulation (91 grams of mung bean flour and 39 grams of plantain peel puree) with a moisture content of 35.30%, ash content of 1.18%, total fat content of 12.68%, protein 8.60%, carbohydrates 42.24%, total energy 317.48 Kcal/100 g, and energy from fat 114.12 Kcal/100 g. For Potassium and Sodium content, namely 251.07 mg/100 g and 46.58 mg/100 g. It is necessary to conduct further research on the effect of giving green bean flour brownies and plantain peel puree on the prevention of hypertension those without other complications for the elderly, both male and female.